Pump user's handbook : life extension - Bloch, Heinz P., 1933- (Fairmont Press ; Distributed by CRC Press/Taylor & Francis, 2006)
"This fully revised edition explains how to achieve consistently superior run lengths, low maintenance expenditures, and unexcelled safety and reliability in all of your pump applications. Written by two practicing engineers whose combined 80-year working careers included all facets of pumping technology, this practical desk reference conveys in detail what facilities must do to rapidly accomplish both superior performance and low life cycle cost for pumps of all types and sizes. Aimed at operating technicians, maintenance professionals, project engineers, reliability engineers and managers, this book is intended for every job function that comes in contact with process pumps. Many industries can reap benefits from using this valuable reference book. Utilities, power generation facilities, pump and paper plants, consumer product manufacturers, pharmaceutical plants, mining operations, chemical and petrochemical plants, municipal works, oil and gas pipelines and oil refineries are among those that will profit from implementing the guidelines described in this text."--Jacket